Impacts of Climate Change on Economic Growth: Empirical Evidence from the Asian Region - Ahmed Gulzar; Aziz, Babar (iRASD Journal of Economics, 2023)
This Panel data study analyzed the long-run effects of anthropogenic climate change on economic growth in Asia during the period 1971-2021 using PMG-ARDL approach. The Panel consisted of thirty one countries from the whole Asian region. The empirical results of the study highlight four key findings. First, the rising temperature impacts economic growth negatively at national level and positively in urban agglomerations, where the latter impact is smaller. Second, the overall net effect of rising temperature on economic growth is negative. Third, the impact of rising rainfall in urban agglomerations is found to be negative on economic growth. Fourth, in long run, the effect of temperature on economic growth, in absolute terms, remained to be the highest among other key factors in the model including exports, gross capital formation, government expenditures and private consumption. These findings highlight the crucial role of climate change in sustainable economic growth and explain substantially the higher negative effects of future climate change in selected Asian countries. The study concludes that efforts are required both at national and regional levels to limit the temperature levels through mitigation and adaptation measures as agreed upon by United Nations’ member countries under Paris Agreement 2017 in order to achieve sustainable economic growth.